Perilaku Organisasi dalam Manifestasi Sumber Daya Manusia yang Capable - Shodiq Taufiq; Wahibah Masula (JUMPA : Jurnal Manajemen Pendidikan, 2022)
This research was conducted to obtain information about Management of Madrasah Organizational Behavior at Madrasah Tsanawiyah (MTs) Sirajul Ulum Krejengan in 2021/2022. This research formulates how the management of madrasah organizational behavior at MTs 2021/2022 in realizing human resources, obstacles and solutions. Research objectives 1) describe the management of madrasah organizational behavior at MTs 2021/2022 in realizing human resources. 2) Analyze the obstacles and solutions in this study. The results of the study reveal (1) Management of Madrasah Organizational Behavior at Tsanawiyah (MTs) Sirajul Ulum Krejengan in realizing human resources which is carried out by planning; carried out by conducting an analysis of all activities or workload of intellectual capacity, capability, work experience and example. Recruitment; prioritizing academic and non-academic achievements, having good morals, and putting aside kinship and prioritizing achievement and professionalism. Development; changing behavior so that changes occur and there is improvement through workshops, training and training. Supervision; carried out according to the schedule once a month in the entire series of school activities, the condition of students, infrastructure, teachers, programs, facilities. Evaluation; three stages, namely monthly, midterm and end of semester, as well as the end of the academic year. Obstacle; teaching staff do not meet what is needed, are not graduates of teacher education, teachers who have taught are not in accordance with their fields, lack of supervision, lack of capacity building, and lack of evaluation. Solution; recruitment management with academic and non-academic selection, training teacher development, workshops, supervision and attention to the organization.